A181: Evaluating Decision‐Making in a Pediatric Rheumatology Clinic. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - David, Jennie G.; Langer, David A.; Kelso, Gwendolyn; Lo, Mindy S.
Abstract : Background/Purpose: Children with rheumatic disease often have chronic needs that require comprehensive, lifelong medical care. Transition of adolescent rheumatology patients from pediatric to adult institutions, in addition to a shift in legal responsibility, calls for the development and activation of medical decision‐making skills. Medical decision‐making is the umbrella term for the dynamic and evolving process of arriving at a medical decision, and is comprised of multiple factors including adherence, self‐management, patient activation, health consciousness, and patient empowerment. This study assessed adolescent and caregiver medical decision‐making characteristics in the outpatient Rheumatology clinic of a pediatric tertiary care hospital. We hypothesized that (1) pediatric patients who are more involved in their care have lower decisional conflict (i.e., conflict over making a medical decision), (2) adolescents want to be involved in their care, and (3) higher health consciousness is positively correlated with valuing involvement in medical decision‐making, actual involvement in decision making, and lower decisional conflict. Methods: This was an anonymous survey study of adolescent patients with chronic rheumatologic illness and their caregivers presenting to the outpatient Rheumatology clinic at Boston Children's Hospital. Both adolescent and caregiver surveys included measures pertaining to health consciousness, medical values, potential barriers to involvement in care, decisional conflict, perceived actual involvement, and desired involvement. Results: A total of twenty‐eight adolescent'caregiver pairs completed the survey. The mean age of adolescents was 16.14 years old ( SD = 2.5). There was a significant positive correlation between adolescent and caregiver health consciousness (r = 0.43, p = 0.027). Valuing involvement in medical decision‐making by adolescent patients was positively correlated with their perception of actual involvement (r = 0.39, p = 0.04) and with their level of health consciousness (r = 0.48, p = 0.009). Furthermore, adolescent perception of actual involvement in medical decision‐making correlated negatively with their feelings of decisional conflict (r = −0.64, p <0.001). Conclusion: Adolescent patients with chronic rheumatic disease have considerable motivation for involvement in care. Given the link between treatment adherence and medical decision‐making, the characteristics of medical decision‐making in the pediatric rheumatology population are a valuable area for future research.